2019
DOI: 10.1029/2019ja027028
|View full text |Cite
|
Sign up to set email alerts
|

MMS Observations of Whistler and Lower Hybrid Drift Waves Associated with Magnetic Reconnection in the Turbulent Magnetosheath

Abstract: Magnetic reconnection (MR) and the associated concurrently occurring waves have been extensively studied at large-scale plasma boundaries, in quasi-symmetric and asymmetric configurations in the terrestrial magnetotail and at the magnetopause. Recent high-resolution observations by MMS (Magnetospheric Multiscale) spacecraft indicate that MR can occur also in the magnetosheath where the conditions are highly turbulent when the upstream shock geometry is quasi-parallel. The strong turbulent motions make the boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The finite plasma beta effect would reduce the maximum growth rate of electrostatic LH waves by a factor (1 + i /2) −1/2 , if T e ≪ T i and V E < v i (Davidson et al, 1977), but it does not stabilize the instability. Therefore, LH waves can survive at the magnetosheath separatrix with a finite plasma beta at ∼5.4, and LH waves under similar plasma beta conditions have been reported in the magnetosheath reconnection (Vörös et al, 2019) and in the magnetotail plasma sheet (Zhou et al, 2014).…”
Section: Discussion and Summarysupporting
confidence: 57%
“…The finite plasma beta effect would reduce the maximum growth rate of electrostatic LH waves by a factor (1 + i /2) −1/2 , if T e ≪ T i and V E < v i (Davidson et al, 1977), but it does not stabilize the instability. Therefore, LH waves can survive at the magnetosheath separatrix with a finite plasma beta at ∼5.4, and LH waves under similar plasma beta conditions have been reported in the magnetosheath reconnection (Vörös et al, 2019) and in the magnetotail plasma sheet (Zhou et al, 2014).…”
Section: Discussion and Summarysupporting
confidence: 57%
“…First, the bow shock and the magnetopause influence the magnetosheath turbulence properties (Gurnett et al 1979;Rezeau & Belmont 2001;Sahraoui et al 2006;Rakhmanova et al 2018b). Second, strong temperature anisotropy generally observed in the magnetosheath can generate various instabilities under different conditions, likely the Alfvén/ ion-cyclotron instability, the mirror-mode instability, the fast magnetosonic/whistler instability, and the fire-hose instability (e.g., Southwood & Kivelson 1993;Quest & Shapiro 1996;Gary et al 1998;Hellinger & Matsumoto 2000;Guicking et al 2012;Kunz et al 2014;Verscharen et al 2016), which is verified by many studies (e.g., Anderson & Fuselier 1993;Anderson et al 1994;Schwartz et al 1996;Czaykowska et al 2001;Lucek et al 2001;Sahraoui et al 2006;Chen & Boldyrev 2017;Teh & Zenitani 2019;Vörös et al 2019;Zhao et al 2019aZhao et al , 2019b. Third, other turbulent fluctuations related to local structures, e.g., current sheets, magnetic islands, and vortices, can further complicate the magnetosheath turbulence picture (e.g., Alexandrova 2008;Karimabadi et al 2014;Huang et al 2018).…”
Section: Introductionmentioning
confidence: 72%
“…The fact that PSP encounters quasi-parallel whistler waves at the boundary of the current sheet, right after the steepest variation in B L , could indicate that the spacecraft was close to the iondiffusion region on that side of the current sheet (e.g. Vörös et al 2019). We checked the trajectory of the probe in the LMN frame and found that its 2D projection in the LN plan is oblique.…”
Section: Event 3 On November 1 2018 At 18:18 Utmentioning
confidence: 99%
“…Quasi-parallel whistlers are often observed in the vicinity of reconnection regions (e.g. Wei et al 2007;Fujimoto & Sydora 2008;Graham et al 2016;Huang et al 2017;Vörös et al 2019). No such clear wave packet was observed at the leading edge.…”
Section: Event 3 On November 1 2018 At 18:18 Utmentioning
confidence: 99%